Efeitos do regime hidrológico sobre comunidades de macrófitas aquáticas na APA Rio Pandeiros, MG, Brasil - Medeiros, Guilherme Ruas (2019)
The diversity of aquatic macrophytes is associated to the heterogeneity habitats and the wetlands are favorable to the development of several life forms of the species and contribute with nutrients and organic matter to the aquatic ecosystems during their decomposition, besides presenting high biomass and high productivity. The wetland area of the Pandeiros River, located in the north of Minas Gerais, is unique in the state, presenting a high diversity of macrophytes and serving as a refuge for several other species of the fauna. The study was carried out between September 2017 and August 2018, contemplating a hydrological cycle. Data collection was carried out in environments with lotic and lentic characteristics, which are predominant in the wetland area, being represented respectively by the bed of the Pandeiros river and its adjacent areas composed predominantly of marginal lagoons and marshes. The research evaluated the dynamics of the community of aquatic macrophytes in this region, focusing its relation with the hydrological dynamics and limnological characteristics of the area. The lentic environment presented a more eutrophic condition in relation to the lotic with higher concentrations of total phosphorus and nitrogen during the evaluated period. The macrophyte mass decay was different among the evaluated environments, occurring more intensely in the lentic environment, contributing to the accumulation of debris as a function of decomposition, contributing to the total nitrogen and phosphorus contribution in the water. Regarding the seasonal variation of Eichhornia azurea biomass, there were no significant differences between the lotic and lentic conditions, however in both areas, there was an increase of biomass in the rainy season, indicating the pulse as a condition for such an increase. The wetlands Pandeiros has a dendritic pattern, the river bed is well delimited in all its extension, and topographic characteristics contribute to the formation of a floodplain in the surroundings along the channel down to the confluence with the São Francisco river, providing connectivity between the lotic and lentic environments. The occurrence of different life forms in the evaluated areas. The absence of water flow in the lentic condition of the upstream and downstream areas evaluated provided a relatively constant pattern in the diversity of life forms present, as well as the establishment of more species. At the points present in lotic conditions, the species present were more susceptible to the pulses, thus providing an environment with lower diversity of life forms of aquatic macrophytes comparison with to the lotic environment and also lower species similarity between upstream and downstream stretches, caused by greater vulnerability to the fixation of some species, especially those with free and fixed floating life forms. The floodplain of the Pandeiros River in Minas Gerais presents a large occurrence of the E. azurea macrophyte under the lotic and lentic conditions, predominant characteristics in the region. As a wetland, the number of researches developed in the region is still scarce, a pre-condition for understanding a series of ecosystem services and their importance as an aquatic ecosystem vulnerable to environmental impacts at regional and global levels.